A Língua Espanhola na fronteira Brasil-Peru: ações políticas no Ensino de Línguas - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This work aims to investigate how the Spanish language teaching was implemented in the public schools of the urban area of Benjamin Constant city, Brazil-Peru border, in the State of Amazonas, seeking to identify the main strategies adopted by public entities responsible for formal education in Elementary School and High School in the city for the implementation of Spanish-language teaching. Thus, we have outlined an evolutionary outlook in Spanish language offer in Benjamin Constant's public school system, from the beginning of its municipal and state public schools offers in the city until the year of 2016, in addition to point out the aspects that have made and make important, to the local educational context, the adoption of the Spanish Language by the municipal and state public schools and, how the political actions on language are embedded in this scenario. In the meantime, we used bibliographical research and documents, In the first part, we have made a survey of theoretical basis on linguistic policies and planning, as well as glotopolytic, on issues involving the teaching of languages in the national, regional and local context, evidencing the Spanish Language. In order to do so, we have collected documents which consists in the corpus of the investigation, along with the municipal and state educational institutions of the city and the Municipal Secretary of Education of Benjamin Constant. Besides, we investigated some data in the Institute of Nature and Culture about the teacher training in Language Spanish, through the Pedagogical Project of Course of Degree in Portuguese Language and Literature and Spanish Language and Literature. As a theoretical basis, we adopted postulates on the topic of linguistic and educational policies, on the glotopolytic, about power relations in politics and linguistic planning, on the Spanish language in Brazil, in Amazonas and in the city of Benjamin Constant. The analysis of the data presented in the documents showed that at first the Foreign Language prevailed in the public school system of Benjamin Constant was English, this occurred only in the teaching previously known as Secondary or Magisterium, nowadays known as High School. In Primary Education there was no offer of any foreign language, however, from the second half of the nineties of last century, the state and municipal public schools of Benjamin Constant began to offer Spanish Language teaching. By the municipality, the first school which offered Foreign Language was the Municipal School Professor Graziela Corrêa de Almeida in 1998, in three classes of the 5th grade of Elementary School, and by the state network of education, the first one which offered Spanish Language was The State School Imaculada Conceição in 1997, in a single class of 1st grade in High School.
Keywords: Ensino de Espanhol; Políticas Linguísticas; Glotopolítica; Fronteira Brasil-Peru; Benjamin Constant - AM; Spanish Teaching; Linguistic Politics; LINGUÍSTICA, LETRAS E ARTES: LETRAS